ANALYSIS OF COFFEE CONSUMPTION PATTERNS AS A RISK FACTOR FOR CHRONIC KIDNEY FAILURE IN DR. SOEROTO NGAWI HOSPITAL - Hidayah, Nurul (Universitas Airlangga, 2022)
Introduction: Chronic Kidney Failure (CKD) is a chronic degenerative disease that requires great attention, this is because its incidence continues to increase, and requires very large treatment time and costs. The most effective therapy for chronic kidney failure is the prevention of risk factors, one of which is the habit of consuming coffee that contains high caffeine. Caffeine in coffee can increase renin resulting in increased blood flow and decreased glomerular filtration rate. The aim of this research is to analyzed the pattern of coffee consumption as a risk factor for chronic kidney failure in Dr. Soeroto Ngawi Hospital. Methods: This research method is correlation with case control approach. The sample in this study consisted of: 34 respondents in the case group, 34 in the control group (sick), and 34 respondents in the control group (healthy). The sampling technique was purposive sampling. Univariate data analysis using descriptive statistics and bivariate analysis using chi square test. Results: The results of the study that coffee consumption habits affect the incidence of chronic kidney failure with a p value of 0.03 (<0.05). Conclusions: The habit of consuming coffee affects the incidence of chronic kidney failure.